The Paradox Of Indonesia's Free And Active Foreign Policy In The Transitional Forum Of The Palestinian Board Of Peace: A Critical Analysis Of Fiqh Siyasah And Islamic Liberation Theology - Rodiatun Mardiah; Fauzan Addinul Jihad; Sultan Maulana Masyriqi (Universitas Jenderal Ahmad Yani, 2026)
Indonesia's involvement in the Palestinian Board of Peace (BoP), signed in Davos in early 2026, has sparked multidimensional controversy. This study aims to analyze the dynamics, implementation, and anatomy of the paradox within Indonesia's free and active foreign policy regarding the Palestinian BoP through the lens of Islamic law and morality. Utilizing a descriptive-critical qualitative method, this study dissects specific primary data in the form of state documents (the President's Speech at the 2024 D-8 Summit, official claims of the 2026 Davos BoP), civil society archives (the 2026 YLBHI Press Release), and philanthropic institutional reports (BAZNAS and Dompet Dhuafa). The results show that the government exercises dual-track diplomacy through transformative demands at the D-8 Summit and pragmatic participation in the Davos BoP. However, the involvement in Davos triggers a paradox because the reconstruction draft of